2005
DOI: 10.1037/1524-9220.6.2.83
|View full text |Cite
|
Sign up to set email alerts
|

The Drive for Muscularity and Masculinity: Testing the Associations Among Gender-Role Traits, Behaviors, Attitudes, and Conflict.

Abstract: Prior qualitative research has suggested that people assume muscular men are more masculine. This assumption was tested quantitatively in 2 studies. In Study 1, men and women completed measures of gender-role traits and behaviors, whereas in Study 2, men completed measures of gender-role conflict and traditional attitudes about men. Study 1 revealed a correlation between self-rated male-typed traits and behaviors, with a need to be more muscular for both men and women. In Study 2, men with more traditional att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
183
2
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(202 citation statements)
references
References 46 publications
(64 reference statements)
12
183
2
5
Order By: Relevance
“…A motivation underlying body image concerns is the desire for a particular body shape, and the body shape that men regularly desire involves muscularity (Cafri et al, 2005;McCreary et al, 2005). This desire for a muscular body is referred to as 'Drive for Muscularity' (DM), and is described as a preoccupation with attaining large muscles concentrated on one's upper body (McCreary, Sasse, Saucier, & Dorsch, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A motivation underlying body image concerns is the desire for a particular body shape, and the body shape that men regularly desire involves muscularity (Cafri et al, 2005;McCreary et al, 2005). This desire for a muscular body is referred to as 'Drive for Muscularity' (DM), and is described as a preoccupation with attaining large muscles concentrated on one's upper body (McCreary, Sasse, Saucier, & Dorsch, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that men's desire to be more muscular is closely associated with male gender role norms, particularly involving masculinity (Hunt, Gonsalkorale, & Murray, 2013;Mahalik et al, 2003;McCreary, Saucier, & Courtenay, 2005). To assess men's conformity to masculine gender roles, Mahalik and colleagues (2003) developed specific conformity to masculine norms (CMN) subscales, and found that the Winning norm subscale, which assesses the drive to win (e.g., In general, I will do anything to win") was uniquely associated with DM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social weight pressures from family members, peers, and the media increases boys' (a) awareness of their appearance as it relates to gender-norms of masculinity (McCreary, Saucier, & Courtenay, 2005), (b) investment in societal appearance norms (Gulas & McKeage 2000), (c) concerns about the adequacy of their bodies (Didie, Kuniega-Pietrazak, & Phillips, 2010), and (d) motivation to reduce discrepancies between their appearance and the societal ideal (Higgins, 1987;Maner, DeWall, Baumeister, & Schaller, 2007). These messages and pressures shape boys' views of their bodies, increase the likelihood of their internalizing societal appearance standards and becoming dissatisfied with their body size and shape, and elevate their risk for restricting their caloric intake in hopes of achieving the lean body ideal .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, adolescent girls have been found to be more likely than boys to restrict their diets (54% girls, 24% boys), use diet products (10% girls, 4% boys), purge (8% girls, 3% boys), and engage in weight-control-motivated exercising (67% girls, 47% boys). 5 In line with societal masculinity norms, men who endorse high levels of drive for muscularity also express high desire to gain weight in muscle, 6 and, unlike adolescent girls, boys report elevated body dissatisfaction at low BMIs. 7,8 Previous research in other health domains has found differences by gender expression --that is, the degree to which one presents oneself in a way consistent with culturally defined expressions of masculine or feminine --in problem drinking 9 and violence perpetration.…”
Section: Introductionmentioning
confidence: 95%